Rabbit meat perceptions and consumption determinants among households in Nakuru County, Kenya - Muchira, Anthony; Mutai, Benjamin; Muange, Elijah (Open Access Research Journal of Science and Technology, 2025)
The concept of the livestock revolution highlights significant changes in global animal production systems, driven by population growth, urbanization, and rising per capita incomes. This has resulted in unprecedented growth in the demand for animal-origin foods, particularly in developing countries. As a result, there is an urgent need for sustainable and nutritious alternatives to conventional livestock. Rabbit meat offers a viable solution due to its superior nutritional profile that includes high protein, low cholesterol, and essential vitamins. Despite its benefits, consumption of rabbit meat remains low compared to popular types of meat. Most of the previous research on rabbits has focused on production aspects and there is limited information on the current status of rabbit meat consumption. This study examines household perceptions and factors influencing rabbit meat consumption in Nakuru County, Kenya. Data was collected from 196 households using semi-structured questionnaires administered through face-to-face interviews. Data was analyzed using descriptive statistics and the double hurdle model. The study found that perceptions of rabbit meat by respondents were generally positive. Regression results show that decision to consume rabbit meat was influenced positively by respondent’s awareness of rabbit meat's nutritional benefits, perceived taste, knowing a rabbit keeper and distance to the market, and negatively by respondent’s age and level of education. Intensity of consumption was positively influenced by affordability of the meat and distance to market, but negatively by age and household size. The study recommends improving rabbit meat’s market accessibility and affordability and increasing awareness on its nutritional benefits be pursued.
Keywords: Rabbit meat; Consumption; Perceptions; Awareness; Nutritional benefits